Autumn and Winter Movements and Sexual Segregation of Willow Ptarmigan - Gruys, Rogier C. (ARCTIC, 1993)
Ptarmigan (Lagopus lagopus alexandrae) in northern British Columbia leave their breeding areas during autumn and winter. The movements differ between males and females. In this study I examine the causes and extent of these differences. Ptarmigan did not leave their breeding grounds immediately after the breeding season, but remained on or near their territories until December. After chicks fledged, part of the population moved uphill from their territories. Coincident with moult into winter plumage, ptarmigan moved farther from their territories. Both movements were probably to areas with better protection against predators. After moulting, all tagged males and half of the tagged females returned to their territories, and males resumed territorial display. Ptarmigan remained on their territories until increasing snow cover depleted cover, forcing them to leave. Males left the breeding grounds later than females and returned earlier in spring. In winter females moved farther than males, supporting the reproductive strategy hypothesis, but segregation was not complete. Sexual segregation may not be related to migration alone, but could occur at any time ptarmigan are in flocks.Key words: willow ptarmigan (Lagopus lagopus alexandrue), autumn territoriality, winter movements, sexual segregation, northern British Columbia Le lagopède des saules (Lagopus lagopus alexandrae) de la Colombie-Britannique septentrionale quitte son aire de nidification durant l'automne et l'hiver. Les déplacements du mâle diffèrent de ceux de la femelle. Ces recherches portent sur le degré et les causes de cette différence. On a trouvé que le lagopède ne quitte pas son aire de nidification immédiatement après la saison nidificatrice. Il reste sur son territoire ou à proximité jusqu'au mois de décembre. Après que les jeunes se sont emplumés, une partie de la population migre vers un territoire plus élevé. En même temps qu'il revêt son plumage d'hiver, le lagopède s'éloigne de son territoire. Ces deux mouvements se font probablement en ...